2013
DOI: 10.1158/1078-0432.ccr-12-1451
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Pathways: MERTK Signaling in Cancer

Abstract: MERTK is a receptor tyrosine kinase of the TAM (Tyro3, Axl, MERTK) family, with a defined spectrum of normal expression. However, MERTK is overexpressed or ectopically expressed in a wide variety of cancers, including leukemia, non-small cell lung cancer, glioblastoma, melanoma, prostate cancer, breast cancer, colon cancer, gastric cancer, pituitary adenomas, and rhabdomyosarcomas, potentially resulting in the activation of several canonical oncogenic signaling pathways. These include the mitogen-activated pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
83
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(86 citation statements)
references
References 58 publications
3
83
0
Order By: Relevance
“…2,11 Linger et al 12 reported that Mer is overexpressed on pre-B-cell ALL (B-ALL) cells of pediatric patients with t(1;19)(q23;p13) translocation. Furthermore, inhibition of Mer by RNA interference (RNAi) reduced survival and chemoresistance of pre-B-ALL cell lines and prolonged survival of xenografts.…”
Section: Key Pointsmentioning
confidence: 99%
See 2 more Smart Citations
“…2,11 Linger et al 12 reported that Mer is overexpressed on pre-B-cell ALL (B-ALL) cells of pediatric patients with t(1;19)(q23;p13) translocation. Furthermore, inhibition of Mer by RNA interference (RNAi) reduced survival and chemoresistance of pre-B-ALL cell lines and prolonged survival of xenografts.…”
Section: Key Pointsmentioning
confidence: 99%
“…[1][2][3] The TAM receptor family consists of Tyro3, Axl, and Mer 4 which all have been found to have transforming properties. [5][6][7] Mer expression has been shown on macrophages, natural killer (NK) cells, dendritic cells, megakaryocytes, and platelets, 8 but it is not known to be present on normal T and B lymphocytes at any stage of differentiation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, studies have found the same oncogenic mutations in both MM and melanoma. 19,32,33,41 We found an association between prior malignancy and the development of respiratory malignancies in MM patients. To our knowledge, MM patients have not been found to have increased risk of developing respiratory malignancies; on the contrary, data from the Surveillance, Epidemiology, and End Results database suggest reduced incidence in MM patients.…”
Section: Discussionmentioning
confidence: 71%
“…1 These studies have a small number of patients that developed second malignancies, 49 and 59 patients, respectively. Underlying explanation for our findings, that a prior malignancy increases the risk of second malignancies in MM patients, could include genetic susceptibilities, [17][18][19][20][21][22][32][33][34][35] immunosuppression, [36][37][38] and therapy-related cancers. 12,13,39 We found MM patients with a prior cancer diagnosis to have an increased risk of developing hematological malignancy, melanoma, nonmelanoma skin cancer, and respiratory malignancy compared with MM patients who did not.…”
Section: Discussionmentioning
confidence: 99%